High-strength and high-conductivity copper alloy material and preparation method thereof

By regulating the types of nano-scale reinforced phases and the amount of elements added in copper alloys, combined with combined deformation heat treatment and pre-aging technology, the problems of the reduction in conductivity and difficult production of existing high-strength and high-conductivity materials are solved, and the high strength and high conductivity are achieved, which is suitable for industrial production.

CN119736515AActive Publication Date: 2025-04-01CENT SOUTH UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411936555.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-01
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

While improving the mechanical properties of existing high-strength and high-conducting copper alloy materials, the conductivity is difficult to maintain, and industrial production is difficult, and there is a lack of an effective strengthening mechanism.

Method used

By regulating the types and addition amount of alloy elements, the types of nano-scale reinforced phases are increased, and by combining deformation heat treatment and pre-aging processes, the precipitation and dislocation proliferation of elements are promoted, forming a microstructure with multi-mechanism coordinated reinforcement.

Benefits of technology

It has achieved the ability to significantly improve the mechanical properties of copper alloys while ensuring that the conductivity does not deteriorate drastically, and obtain excellent comprehensive performance, which is suitable for industrial-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119736515A_ABST
    Figure CN119736515A_ABST
Patent Text Reader

Abstract

The invention discloses a high-strength and high-conductivity copper alloy material and a preparation method thereof, and is characterized in that elements such as Cr, Hf, P, Ce, Zn, Ag and the like are added into copper according to the precipitation characteristics of precipitation strengthened copper alloy, so that the precipitated phase of the alloy is regulated and controlled, and a matrix is strengthened by two nanoscale strengthening phases; the mechanical property, the electrical property and the softening resistance of the alloy are improved; after traditional solution treatment, pre-aging treatment, pre-cooling deformation treatment and regression treatment are added, alloy grains can be effectively refined, the precipitation sequence of multi-nanoscale strengthening phases is regulated and controlled, and the strengthening effect of the precipitation strengthening phases is reserved as much as possible. And the high-strength and high-conductivity copper alloy material is obtained through combined deformation heat treatment, and the high-strength and high-conductivity copper alloy material has the excellent mechanical property (700 MPa or above) and the excellent electrical property (70% IACS or above).
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of copper alloy processing, and in particular relates to a high-strength and high-conductivity copper alloy material and a preparation method thereof. Background Art

[0002] Copper alloys are functional structural materials with high strength, excellent electrical and thermal conductivity, good wear resistance and corrosion resistance, and are widely used in energy and power, electronics and electrical appliances, transportation, marine engineering and other fields. With the rapid development of high-tech industries such as 5G electronic communications, new energy vehicles, very large-scale integrated circuits, and high-speed rail transportation, the demand for copper alloys, especially copper alloys with special properties of high strength and high conductivity, is increasing, and higher requirements are put forward for the comprehensive performance of copper alloy materials. Under the premise of ensuring the comprehensive performance of high strength and high conductivity, it has excellent anti-softening performance and can serve in harsh high-temperature environments.

[0003] Traditional high-strength and high-conductivity copper alloys often improve the mechanical properties of copper alloys at the expense of some electrical conductivity. Although the introduction of a large number of elements into copper alloys can strengthen the matrix by solid solution strengthening, the solid solution elements will greatly destroy the periodic potential field of the metal crystal, significantly reducing the electrical conductivity of the alloy. The synergistic addition of elements that can be precipitated in the form of a single substance or an intermetallic compound, and the use of combined deformation-aging and other deformation heat treatment methods can promote the dissolution of the added elements from the matrix in the form of a strengthening phase, which can purify the matrix to a certain extent and achieve a simultaneous increase in electrical conductivity and mechanical properties. However, this method has its upper limit. It is limited by the solid solubility, and the purification and strengthening effects that can be achieved cannot be endlessly improved.

[0004] The Cu-Zn, Cu-Mg, and Cu-Zr alloys developed in the early stage of high-strength and high-conductivity copper alloy development used solid solution strengthening as the main strengthening mechanism, and both strength and conductivity were difficult to satisfy. Although the more widely used precipitation-strengthened Cu-Fe-P, Cu-Ni-Si, and Cu-Cr alloys have achieved generational progress in comprehensive performance, they also have certain defects and their own performance limits. Although the high mass percentage of Si added to the Cu-Ni-Si alloy provides sufficient precipitation power for Ni2Si, the residual Si atoms in the copper matrix seriously deteriorate the electrical conductivity of the alloy, and the electrical conductivity is difficult to exceed 50% IACS; the Fe element in the Cu-Fe-P alloy has limited strengthening effect on the alloy. When the addition amount is small, the electrical conductivity can reach 90% IACS, but the strength is only 450MPa. Although increasing the addition amount can improve the strength at the expense of part of the electrical conductivity, it is often not worth the loss. The tensile strength is difficult to break through 600MPa, and the electrical conductivity also drops below 80% IACS; the Cr phase precipitated in the Cu-Cr alloy will be significantly coarsened with the extension of aging time and the increase of aging temperature, and the contribution to the mechanical properties of the alloy is greatly reduced, making it difficult for the tensile strength to exceed 630MPa.

[0005] Although the tensile strength of Cu-Fe-P and Cu-Cr systems can be improved to a level that is difficult to achieve with conventional deformation methods through some extreme deformation conditions (deep cold deformation, severe plastic deformation, etc.), and thus achieve excellent comprehensive performance, the performance improvement brought about by extreme deformation conditions is achieved at the expense of the possibility of industrial large-scale production. How to achieve high strength and high conductivity at the same time and obtain high-performance copper alloys with good comprehensive performance has always been a hot topic and difficulty in research, and it is also a symbol of the technical level of the high-performance copper processing industry. This forces us to develop new high-performance copper alloy systems to meet the high-performance requirements put forward by modern industry and high-tech industries. Summary of the invention

[0006] In view of the shortcomings of the prior art, the first object of the present invention is to provide a high-strength and high-conductivity copper alloy material. The copper alloy material provided by the present invention adopts a strengthening idea different from that of the traditional high-strength and high-conductivity copper alloy. By adjusting the types and addition amounts of alloy elements, while increasing the types of the main nano-scale strengthening phases of the alloy, a large amount of precipitation of the added elements can be ensured. Under the premise of ensuring that the electrical conductivity of the copper alloy does not deteriorate drastically, the mechanical properties of the alloy are greatly improved, so that the alloy exhibits excellent comprehensive properties.

[0007] The second object of the present invention is to provide a method for preparing a high-strength and high-conductivity copper alloy material. Compared with conventional traditional preparation methods, the preparation method provided by the present invention is simple and controllable while improving the comprehensive performance of the alloy, and is adapted to the specific conditions of industrial production, and is suitable for industrial-scale production. Through the preparation method of the present invention, it is possible to prepare an alloy with finer grains, and enhance the contribution of the fine grain strengthening mechanism to the mechanical properties of the alloy. At the same time, it can provide sufficient precipitation power and promote the precipitation of precipitation phases in a large range, so that the alloy can obtain more excellent comprehensive performance. The improvement of the comprehensive performance does not produce selectivity due to the difference in the composition of the precipitation-strengthened high-strength and high-conductivity copper alloy, and has a universal strengthening effect. In addition, the preparation method provided by the present invention has an additional organizational regulation effect on the multi-nanoscale strengthening phase copper alloy material provided by the present invention, and can regulate the precipitation order of the precipitation phase.

[0008] In order to achieve the above object, the present invention adopts the following technical solution:

[0009] The present invention provides a high-strength and high-conductivity copper alloy material. The copper alloy material is composed of the following by mass percentage: 0.4-1.5wt% Cr, 0.6-1.5wt% Hf, 0-0.02wt% P, 0-0.15wt% Ce, 0-0.2wt% Zn, 0-0.2wt% Ag, and the balance is Cu.

[0010] The copper alloy material provided by the present invention is a CuCrHf alloy material, and Cr and Hf in the CuCrHf alloy are both main added elements, which are the source of the high-strength and high-conductivity copper alloy material in the present invention being superior to conventional copper alloys. The composition design of traditional high-strength and high-conductivity copper alloys is centered on a certain nano-strengthening phase, and other elements are selected with the strengthening idea of ​​promoting precipitation or modifying the precipitated phase. For example, taking the copper alloy material containing Hf as an example, since the limiting solid solubility of the Hf element in the Cu matrix is ​​limited, the current mainstream use of the Hf element is as a solid solution strengthening element for other alloy systems, with a small amount of addition and limited strengthening effect on the alloy.

[0011] The addition of high-content Cr and high-content Hf elements to the CuCrHf alloy provided by the present invention increases the types of high-density nanoscale strengthening phases in the alloy (Cr phase and CuHf phase), which has more precipitation potential and strength improvement than the traditional high-strength and high-conductivity copper alloy with a single nanoscale precipitation phase as the strengthening phase (Fe phase in Cu-Fe-P alloy, Ni2Si phase in Cu-Ni-Si alloy, and Cr phase in Cu-Cr alloy). It should be pointed out that although the addition amount of Cr and Hf elements is relatively high, the electrical conductivity of the CuCrHf alloy will not be unable to obtain a large increase like the Cu-Ni-Si alloy. This is because the room temperature solid solubility of Cr and Hf elements in copper is close to zero. After the combined deformation heat treatment, the Cr and Hf elements can be fully precipitated from the matrix in the form of precipitation phases, ensuring that the alloy has a high electrical conductivity. The addition of Hf element also has the effect of reducing the stacking fault energy of the alloy, allowing the alloy to form deformation twins during conventional cold rolling deformation, hindering the interaction between dislocations, retaining a higher dislocation density and more substructures in the alloy matrix, increasing the recrystallization temperature and softening resistance of the alloy, and effectively improving the alloy's work hardening rate and final mechanical properties.

[0012] In addition, the present invention further adds trace additive elements P, Ce, Zn, and Ag, which can control the smelting quality or refine the grains on the one hand. For example, the P element can purify the matrix, improve the fluidity of the copper alloy melt, and enhance the casting quality of the ingot; the Ce element can refine the grains; trace Ag and Zn elements have little effect on the electrical conductivity of the alloy, and can achieve solid solution strengthening of the matrix under the premise of slightly losing the electrical conductivity. On the other hand, these trace elements can effectively regulate the morphology of the precipitated phase, so that the CuHf phase and the Cr phase can be more dispersed in the matrix in the form of a spherical phase, thereby improving the comprehensive performance of the alloy.

[0013] With the cooperation of the above components and contents, the alloy of the present invention has excellent comprehensive properties, such as high hardness, high strength, high electrical conductivity and high softening resistance temperature.

[0014] The element content of the alloy of the present invention should be controlled within the scope of the present invention to produce an effective synergistic effect. If the Cr element is too little, it cannot provide sufficient precipitation power, and it is difficult to achieve sufficient strengthening effect and matrix purification effect, so that various performance indicators of the final alloy product are sharply reduced. Excessive Cr elements will cause coarse Cr-rich primary phases to appear in the matrix. This part of the Cr phase increases with the degree of excess, increases in number and size, and has a very limited effect on the strength improvement of the material, and is not conducive to the subsequent preparation and processing technology and grain refinement. If the Hf element is too little, it also cannot provide sufficient precipitation power. Although the added Hf element can play a certain role in solid solution strengthening in the matrix, compared with the aggravation of the electron scattering effect, the slight improvement in strength is far less than the degree of decrease in conductivity. Excessive Hf elements will also increase the number and size of coarse Hf-rich primary phases in the matrix. In severe cases of excessive Hf, CuHf amorphous may even be produced, which is harmful to the comprehensive performance of the material. P, Ce, Ag and Zn are trace elements of the high-strength and high-conductivity copper alloy provided by the present invention, which can improve the smelting quality or regulate the structure of the alloy, and have great significance for the comprehensive performance of the alloy. However, the addition amount should not be too much, especially P, Ce and Zn. Too high content will sharply reduce the conductivity of the alloy, not only without significant strengthening effect, but also deteriorate the comprehensive performance of the alloy. Too little content will not achieve the effect of addition. The addition amount of elements controlled within the scope of the present invention may have little effect on the conductivity, or may be eluted from the matrix, thereby avoiding solid solution in the Cu matrix and increasing the scattering effect of the lattice on electrons.

[0015] In a preferred embodiment, the copper alloy material has the following composition, calculated by mass percentage: Cr 0.4-0.7wt.%, Hf 0.6-0.9wt.%, P 0-0.02wt.%, Ce 0-0.02wt.%, Zn 0-0.02wt.%, Ag 0-0.2wt.%, and the remainder is Cu.

[0016] Further preferably, the copper alloy material, by mass percentage, has the following composition: The copper alloy material, by mass percentage, has the following composition: Cr 0.7wt.%, Hf 0.9wt.%, P 0.02wt.%, Ce 0.01wt.%, Zn 0.01wt.%, Ag 0.02wt.%, and the remainder is Cu.

[0017] According to a preferred embodiment, in the high-strength and high-conductivity copper alloy material, there are interactions between a variety of nanoscale precipitated phases and dislocations, which are mutually pinned and entangled and dispersed in the matrix. The grain size of the high-strength and high-conductivity copper alloy material is ≤30 μm, and twins are contained in the grains.

[0018] The high-strength and high-conductivity copper alloy material provided by the present invention has fine grains, more twins, and there is interaction between high-density multiple nano-scale precipitation phases and high-density dislocations, which pin and entangle each other, indicating that the nano-scale precipitation phase particles can effectively pin the migration of dislocations and improve the strength and toughness of the alloy.

[0019] The present invention also provides a method for preparing a high-strength and high-conductivity copper alloy material. First, various raw materials are prepared according to the designed composition ratio, smelted to obtain an alloy liquid, and the alloy liquid is cast to obtain a copper alloy ingot. The copper alloy ingot is then subjected to homogenization annealing treatment, thermal deformation treatment, and solid solution treatment in sequence to obtain a solid solution alloy material. Finally, the solid solution alloy material is subjected to pre-aging treatment, pre-cooling deformation treatment, regression treatment, and combined deformation heat treatment in sequence to obtain a high-strength and high-conductivity copper alloy material.

[0020] The preparation method of the present invention first uses a medium frequency melting furnace to carry out smelting in an atmospheric atmosphere, and casts the molten metal into a mold to complete the preparation of a copper alloy ingot. Then, the copper alloy ingot is subjected to conventional organizational control, including: homogenization annealing treatment, thermal deformation treatment, and solid solution treatment. After completing these treatments, most of the defects of the casting are eliminated, and the elements added within the scope of the present invention are all dissolved into the matrix of the copper alloy. The purpose of the homogenization annealing treatment is to eliminate the segregation inside the casting grains during the smelting and casting process as much as possible. The thermal deformation treatment is to further eliminate the casting defects of the casting, and the solid solution treatment can effectively form a solid solution of trace elements with the copper matrix. Finally, the alloy that has completed solid solution is subjected to pre-aging treatment, pre-cooling deformation treatment, regression treatment and combined deformation heat treatment to prepare an alloy sample with excellent performance. The processing process of the alloy is the core of this preparation method. The precipitation strengthening phase produced in the aging treatment stage can increase the dislocation strengthening effect produced during the cold deformation treatment, so that large-scale recovery recrystallization occurs rapidly during the regression treatment stage, thereby preparing a pre-aging sample with finer grains, and then applying conventional combined deformation heat treatment to the alloy. The combined deformation heat treatment includes multiple cold rolling and aging, which can promote the precipitation of alloy elements dissolved in the lattice as much as possible, intensify the proliferation of dislocations during the deformation process, and improve the values ​​of precipitation strengthening and deformation strengthening.

[0021] In the present invention, it is crucial to perform pre-aging treatment, pre-cooling deformation treatment, and regression treatment before the combined deformation heat treatment. If the alloy material after the solution treatment is directly subjected to the combined deformation treatment, although a large amount of CuHf phase will be obtained in the matrix, the CuHf phase will precipitate in various morphologies (rod-shaped, spherical, and disc-shaped) and grow and coarsen during the aging process, which greatly weakens the strengthening effect of the matrix. The inventors have found that the regression process can not only refine the grains, but also interrupt the precipitation process of the CuHf phase and regulate the precipitation order, thereby retaining the strengthening effect provided by the nano-scale CuHf phase to the greatest extent. Finally, under the synergistic effect of the trace added elements of the present invention, the CuHf phase and the Cr phase can be dispersed in the matrix in the form of nano-spherical phases, thereby achieving a more excellent strengthening effect.

[0022] Through the above preparation method, the high-density nanoscale Cr phase and CuHf phase can be dispersed in the matrix as the main strengthening second phase of the alloy, and complexed with fine grains and high-density dislocations to form a multi-mechanism synergistic strengthening microstructure feature, thereby giving the prepared CuCrHf alloy excellent mechanical properties, electrical conductivity, and softening resistance. On the one hand, the aging + cold deformation + regression process allows a part of the solid solution elements to be first precipitated from the matrix, becoming a source of dislocation proliferation in the subsequent deformation process and a nucleation point and grain boundary pinning in the regression process, increasing the dislocation density introduced into the matrix by cold deformation, reducing the size of recrystallized grains, and the initial grain size of the alloy is significantly better than that of the untreated solid solution alloy. On the other hand, the Cr and Hf elements dissolved in the matrix can be precipitated from the copper alloy solid solution after cold deformation and heat treatment, and evenly dispersed in the matrix, providing a synergistic solid solution strengthening effect of trace Ag and Zn elements on the matrix, so that the alloy has excellent electrical conductivity while also exhibiting excellent mechanical properties and anti-softening properties.

[0023] According to a preferred embodiment, the smelting process is as follows: pure copper, Cu-Cr master alloy, Cu-Hf master alloy, Cu-Zn master alloy, Cu-P master alloy, pure Ce, pure Ag and pure Zn are prepared according to the designed proportions, pure copper is first melted, then the temperature is raised to 1200-1300°C, pure Ag and pure Zn are added, the temperature is continued to be raised to 1300-1400°C, Cu-Cr master alloy is added in 3-4 batches, the temperature is kept for 2-3 minutes, and then the temperature is stirred for 30-60 seconds, and then Cu-Hf master alloy, pure Ce and Cu-P master alloy are added, the temperature is kept for 1-2 minutes, and then the temperature is lowered to 1200-1300°C while stirring.

[0024] In the present invention, there are relatively more alloying elements, and the material feeding sequence of the above preferred scheme can effectively reduce the burning loss of alloying elements; in addition, since relatively more alloying elements are added, the viscosity of the melt is relatively large during the smelting process, and slag is easily generated, and the added Cu-P intermediate alloy can cooperate with the stirring operation after the step-by-step feeding to effectively alleviate this problem, purify the melt, improve the fluidity of the melt, and thus improve the quality of the ingot; and the stirring during the smelting process, on the one hand, can promote the full melting of the gradually added alloying elements, so that the components in various places in the molten metal are uniform, and on the other hand, it can also alleviate the cooling effect of the step-by-step feeding on the local melt.

[0025] In actual operation, a medium frequency induction furnace is used for smelting in an atmospheric atmosphere, and a graphite rod is used for stirring during the smelting process.

[0026] In a preferred embodiment, the smelting is carried out in an atmospheric atmosphere, and graphite is coated on the melt during the smelting process. By coating the melt with graphite as a deoxidizer, the burnout rate can be reduced.

[0027] In a preferred embodiment, the casting temperature is 1200-1450°C, and the preheating temperature of the mold is 400-500°C.

[0028] In a preferred embodiment, the temperature of the homogenization annealing treatment is 780-980°C, and the homogenization annealing treatment time is 2-8 hours. The purpose of the homogenization annealing treatment is to eliminate the segregation phenomenon in the cast structure and eliminate the heterogeneity of the microstructure as much as possible. The effect of the homogenization annealing treatment is related to the selected system. If the temperature is too high, the alloy is prone to overburning or even melting, and the quality of the cast alloy may even decrease instead of increase. If the temperature is too low, the diffusion of elements is difficult, and even if the holding time of the homogenization annealing treatment is increased, it is difficult to completely eliminate the intracrystalline segregation. The long homogenization time also increases the preparation process and process costs.

[0029] In a preferred embodiment, the thermal deformation treatment is selected from hot forging or hot rolling, the temperature of the thermal deformation treatment is 850-950° C., the total deformation is 50%-90%, and the deformation of each pass is 10%-20%.

[0030] In actual operation, after the homogenization heat treatment is completed, the ingot after homogenization annealing is cooled with the furnace to the temperature required for thermal deformation, and then thermal deformation is performed. Through thermal deformation treatment, the casting defects of the alloy are eliminated as much as possible, dynamic recrystallization of the alloy is promoted, and the coarse grains after melting, casting and homogenization heat treatment are refined.

[0031] In a preferred embodiment, the temperature of the solution treatment is 800 to 1050° C., the time of the solution treatment is 2 to 8 hours, and water quenching is performed after the solution treatment is completed.

[0032] The added alloying elements are all dissolved into the copper alloy matrix through solution treatment, and the supersaturated solid solution state is retained to room temperature through water quenching to provide sufficient precipitation power.

[0033] In a preferred embodiment, the pre-aging temperature is 350-600° C., and the pre-aging time is 5-480 min.

[0034] After the solution treatment, the alloy has enough precipitation power. After aging, a considerable amount of nano-scale CuHf phase and Cr phase has been generated inside the alloy. Combined with the subsequent deformation and regression treatment, better precipitation effect and fine grain effect can be achieved. In actual operation, after aging treatment, the surface defects of the alloy need to be removed and corrected by machining.

[0035] In a preferred solution, the total deformation amount of the pre-cooling deformation treatment is 40% to 90%, and the deformation amount of each process is in the range of 10% to 30%.

[0036] In a preferred embodiment, the temperature of the regression treatment is 750-1000° C., and the treatment time is 10 s-10 min.

[0037] The purpose of regression treatment is to combine the high-density nanophase precipitated during pre-aging and the high-density dislocations introduced during the pre-cooling deformation process, so that the alloy undergoes general recrystallization, the grains become finer, and contribute more to the strength of the alloy, while interrupting the precipitation process of the CuHf phase, thereby retaining the strengthening effect provided by the nano-scale CuHf phase to the greatest extent. The temperature of the regression treatment needs to be within the set range. If the regression temperature is too low, not only will the recrystallization effect not be achieved, but the formation of the precipitated phase can only be regulated. If the regression temperature is too high, secondary recrystallization is likely to occur, and not only will the grain refinement not be achieved, but the structure of the alloy will return to the state of solid solution treatment.

[0038] In a preferred embodiment, the combined thermomechanical treatment consists of alternating cold deformation and aging treatment. In actual operation, the deformation amount and number of cold deformation, the temperature, time and number of aging can be adjusted, and the properties of alloys prepared by different treatment systems are somewhat different. If the number of cold deformation and aging is one, the deformation amount of cold deformation should be 40% to 90%, and the temperature and time of aging are 350 to 600°C, 5 to 480 minutes.

[0039] Further preferably, the combined deformation heat treatment consists of two cold deformations and two aging treatments, wherein the deformation amount of the first cold deformation is 40% to 90%, and the deformation amount of each pass is 10% to 30%. After the first cold deformation treatment, the first aging treatment is performed, and then the second cold deformation treatment is performed. The deformation amount of the second cold deformation treatment is 40% to 90%, and the deformation amount of each pass is 10% to 30%. After the second cold deformation treatment, the second aging treatment is performed, wherein the temperature of the first aging treatment is 350 to 600°C, preferably 450 to 500°C, and the time is 5 to 480 min. The temperature of the second aging treatment is 350 to 600°C, preferably 350 to 450°C, and the time is 5 to 480 min.

[0040] After the regression treatment, combined deformation heat treatment is performed, and finally a large amount of nano-spherical CuHf phase and Cr phase are precipitated and dispersed in the matrix, thereby obtaining a high-strength and high-conductivity copper alloy with the most excellent comprehensive performance.

[0041] The positive beneficial effects achieved by the present invention are:

[0042] (1) According to the preparation and processing technology specified in the present invention, the copper alloy plate prepared after a series of treatments has a conductivity of 70-89% IACS, a hardness of 180-230 HV, a tensile strength of 670-730 MPa, and an elongation of 8.2%-16.7%. While significantly improving the strength of the alloy system, the alloy has excellent plasticity and electrical conductivity. Compared with other high-strength and high-conductivity copper alloys, the alloy prepared by the present invention has excellent comprehensive mechanical properties, enriching my country's high-strength and high-conductivity copper alloy product library.

[0043] (2) The strengthening idea of ​​modifying the precipitated phase with alloying elements was changed. By adding Hf, which forms a single-phase solid solution zone with Cu and Cr, and combining the deformation heat treatment process to control the alloy structure, the composite strengthening effect of two nanoscale strengthening phases was achieved, which greatly improved the comprehensive performance of the alloy and achieved a higher combination of strength and conductivity.

[0044] (3) Improve the overall performance while maintaining the high electrical conductivity of the alloy as much as possible. The fundamental reason lies in the regulation of the microstructure by the alloy elements Hf, P, Ce, Zn, and Ag. The addition of Hf, Zn, and Ag elements has the effect of reducing the stacking fault energy of the alloy, so that the alloy forms deformation twins during conventional cold rolling deformation, improves the strength of the alloy, and can effectively improve the hardening effect of the alloy during subsequent deformation; the P element can purify the melt and make the melt fluidity of the alloy better, and the quality of the alloy ingot obtained by casting is higher; the Ce element can refine the grains.

[0045] (4) The preparation method of pre-aging + pre-cold deformation + regression process + combined deformation heat treatment can maximize the precipitation potential of the alloy. The precipitation phase precipitated by the first aging process can pin the dislocations, and a large number of dislocations can be introduced into the matrix by combining the subsequent cold deformation. The mechanical properties of the alloy are improved by deformation strengthening, precipitation strengthening and a small part of solid solution strengthening. More importantly, the CuHf phase order is regulated by the above process, and a large number of nano-spherical CuHf phases and Cr phases are finally precipitated and dispersed in the matrix, thereby obtaining a high-strength and high-conductivity copper alloy with the best comprehensive performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 This is the preparation process flow of the new high-strength and high-conductivity copper alloy material described in the present invention.

[0047] Figure 2 This is the EBSD result of the copper alloy after solution treatment in Example 1 of the present invention.

[0048] Figure 3 This is the EBSD result of the sample after the copper alloy regression treatment in Example 1 of the present invention.

[0049] Figure 4 This is the hardness change curve of the copper alloy after combined deformation heat treatment in Example 1 of the present invention.

[0050] Figure 5 This is the conductivity change curve of the copper alloy after combined deformation heat treatment in Example 1 of the present invention.

[0051] Figure 6 This is a bright field image of the peak aging of the copper alloy in Example 1 of the present invention. DETAILED DESCRIPTION

[0052] The embodiment of the present invention provides a high-strength and high-conductivity copper alloy material, including appropriate amounts of Cr, Hf, P, Ce, Zn and Ag, which can achieve excellent comprehensive performance. The present invention also provides a preparation process of the high-strength and high-conductivity copper alloy material.

[0053] In order to better understand the above scheme, the present invention is described in detail below in conjunction with the embodiments. In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention can also be implemented in other ways different from those described herein.

[0054] Example 1

[0055] Example 1 A high-strength and high-conductivity copper alloy material is prepared. In terms of mass percentage, the material components include 0.7wt.% Cr, 0.9wt.% Hf, 0.02wt.%, 0.01wt.%, Ce, 0.01wt.%, Zn, 0.02wt.%, and the balance is copper.

[0056] The preparation method of the high-strength and high-conductivity copper alloy selected in Example 1 comprises the following steps:

[0057] 1) Use a medium frequency induction melting furnace to melt in an atmospheric environment to obtain an ingot, and the smelting raw materials are Cu-10wt.%Cr master alloy, Cu-20wt.%Hf master alloy, Cu-20wt.%Zn master alloy, Cu-10wt.%P master alloy, pure Ce, pure Ag, and pure Zn. The raw materials, crucible, and mold are fully preheated, the raw materials preheating temperature is 150°C, and the crucible and mold preheating temperature is 500°C to fully dry.

[0058] There are relatively strict requirements for the feeding sequence of the smelting process, and the quality of the ingot can be effectively improved and guaranteed: first put pure copper into the crucible, start to heat it up, and wait for it to melt (1083℃). When the melt temperature is 1250℃, add pure Ag and pure Zn. When the melt temperature rises to 1400℃, add Cu-Cr master alloy in 3 to 4 batches. After each batch of feeding, keep it warm for 2 minutes and stir it for 60 seconds, and cover the surface of the melt with graphite. Then add Cu-Hf master alloy, pure Ce, and Cu-P master alloy, keep it warm for 2 minutes, stir it for 60 seconds, and pour it after the melt temperature drops to 1250℃.

[0059] 2) The smelted ingot is homogenized and kept at 950°C for 4 hours.

[0060] 3) After the ingot is cooled to 900°C in the furnace, the homogenized billet is subjected to hot processing in the form of hot rolling. The total deformation of the hot rolling is 80%, which is completed in five passes with a deformation of 16% per pass. After the hot rolling, the billet is water quenched.

[0061] 4) The alloy after hot deformation and blanking was subjected to solution treatment at a solution temperature of 950°C, a holding time of 2 h, and water quenching.

[0062] 5) The alloy after solution treatment is pre-aged, the pre-aging temperature is 500°C, the pre-aging time is 60 min, and the cooling method is water quenching.

[0063] 6) The pre-aged alloy is pre-cooled and deformed in the form of cold rolling with a deformation amount of 40% in three passes, and the deformation amount of each pass is controlled between 10% and 15%.

[0064] 7) The pre-aged alloy is subjected to regression treatment at 750°C, with a holding time of 5 minutes and a cooling method of water quenching.

[0065] 8) The alloy with refined grains is subjected to a combined deformation heat treatment, which consists of two deformations and two agings. The plate is cold rolled once at room temperature, with a total cold rolling deformation of 80%, which is completed in three passes, and the deformation of each pass is controlled between 10% and 30%. It is aged once in a furnace at 450°C for 2 hours; it is cold rolled twice at room temperature, with a total cold rolling deformation of 50%, which is completed in three passes, and the deformation of each pass is controlled between 15% and 20%. It is aged twice in a furnace at 350°C for 12 hours, and the new high-strength and high-conductivity copper alloy material studied by the present invention is obtained.

[0066] Figure 1 This is the preparation process route of an embodiment of the present invention.

[0067] Figure 2 This is the EBSD result after solution treatment of Example 1 of the present invention. It can be observed that after solution treatment, the size of the grains is relatively large, about 300 to 400 μm.

[0068] Figure 3 This is the EBSD result of Example 1 of the present invention after a series of grain refinement processes (pre-aging, pre-cooling deformation, and regression treatment). The grains have generally undergone recovery recrystallization, and the grain size has been effectively refined to about 10 to 30 μm.

[0069] Figure 4 and Figure 5 The variation curve of aging hardness and electrical conductivity after combined deformation heat treatment in embodiment 1 of the present invention shows that the alloy has obvious strengthening effect.

[0070] Figure 6 The TEM observation results of the precipitation phase at the peak aging state show that fine and dispersed precipitation phases are distributed in the alloy matrix and have obvious interactions with dislocations, indicating that nano-scale precipitation phase particles can effectively pin the migration of dislocations and improve the strength and toughness of the alloy. The final product has a tensile strength of 760MPa, a hardness of 235HV, and a conductivity of 73%IACS.

[0071] The physical properties of the high-strength and high-conductivity copper alloy material prepared in Example 1 were tested, and the test results are shown in Table 1.

[0072] Table 1 Physical properties of Example 1

[0073] Physical properties Test Results Test Method Room temperature hardness 235HV YS / T471-2004 Room temperature tensile strength 760MPa GB / T34505-2017 Room temperature elongation 11.3% GB / T34505-2017 Room temperature conductivity 73%IACS GB / T32791-2016

[0074] Example 2

[0075] Example 2 A high-strength and high-conductivity copper alloy material is prepared. In terms of mass percentage, the material components include 0.4wt.% Cr, 0.6wt.% Hf, 0.02wt.%, P, 0.02wt.%, Ce, 0.02wt.%, Zn, 0.01wt.%, and the balance is copper.

[0076] The preparation method of the high-strength and high-conductivity copper alloy selected in Example 2 comprises the following steps:

[0077] 1) Use a medium frequency induction melting furnace to melt in an atmospheric environment to obtain an ingot, and the smelting raw materials are Cu-10wt.%Cr master alloy, Cu-20wt.%Hf master alloy, Cu-20wt.%Zn master alloy, Cu-10wt.%P master alloy, pure Ce, pure Ag, and pure Zn. The raw materials, crucible, and mold are fully preheated, the raw materials preheating temperature is 150°C, and the crucible and mold preheating temperature is 400°C to fully dry.

[0078] The feeding order of the smelting process has not changed: first put pure copper into the crucible, start to heat it up, wait for it to melt (1083℃), add pure Ag and pure Zn when the melt temperature is 1250℃, and add Cu-Cr master alloy in 3 to 4 batches after the melt temperature rises to 1400℃. After each batch of materials is added, keep warm for 2 minutes and stir for 60 seconds, and cover the surface of the melt with graphite. Then add Cu-Hf master alloy, pure Ce, and Cu-P master alloy, keep warm for 2 minutes, stir for 60 seconds, and pour after the melt temperature drops to 1250℃.

[0079] 2) The smelted ingot is homogenized and kept at 950°C for 2 hours.

[0080] 3) After the ingot is cooled to 900°C in the furnace, the homogenized billet is subjected to hot processing in the form of hot rolling. The total deformation of the hot rolling is 80%, which is completed in five passes with a deformation of 16% per pass. After the hot rolling, the billet is water quenched.

[0081] 4) The alloy after hot deformation and blanking was solution treated at a solution temperature of 950°C, a holding time of 1 h, and water quenching.

[0082] 5) The alloy after solution treatment is pre-aged, the pre-aging temperature is 500°C, the pre-aging time is 30 min, and the cooling method is water quenching.

[0083] 6) The pre-aged alloy is pre-cooled and deformed in the form of cold rolling with a deformation amount of 40% in three passes, and the deformation amount of each pass is controlled between 10% and 15%.

[0084] 7) The pre-aged alloy is subjected to regression treatment at 750°C, with a holding time of 5 minutes and a cooling method of water quenching.

[0085] 8) The alloy with completed grain refinement is subjected to combined deformation heat treatment, which consists of two deformations and two agings. The plate is cold rolled once at room temperature, with a total cold rolling deformation of 80%, which is completed in three passes, and the deformation of each pass is controlled between 10% and 30%. It is aged once in a furnace at 450°C for 1 hour; it is cold rolled twice at room temperature, with a total cold rolling deformation of 50%, which is completed in three passes, and the deformation of each pass is controlled between 15% and 20%. It is aged twice in a furnace at 350°C for 12 hours, and the new high-strength and high-conductivity copper alloy material studied by the present invention is obtained.

[0086] The physical properties of the high-strength and high-conductivity copper alloy material prepared in Example 2 were tested. The final product had a tensile strength of 673 MPa, a hardness of 206 HV, and a conductivity of 72% IACS. The test results are shown in Table 2.

[0087] Table 2 Physical properties of Example 2

[0088] Physical properties Test Results Test Method Room temperature hardness 206HV YS / T471-2004 Room temperature tensile strength 673MPa GB / T34505-2017 Room temperature elongation 14.7% GB / T34505-2017 Room temperature conductivity 72%IACS GB / T32791-2016

[0089] Comparative Example 1

[0090] The components of the CuCrHf alloy material prepared in Comparative Example 1 are the same as those in Example 1. The raw material preparation and smelting process in the preparation method are the same as those in Example 1, and the specific processing process is as follows:

[0091] 1) Raw material preparation and smelting are the same as in Example 1.

[0092] 2) The smelted ingot is homogenized and kept at 950°C for 4 hours.

[0093] 3) After the ingot is cooled to 900°C in the furnace, the homogenized billet is subjected to hot processing in the form of hot rolling. The total deformation of the hot rolling is 80%, which is completed in five passes with a deformation of 16% per pass. After the hot rolling, the billet is water quenched.

[0094] 4) The alloy after hot deformation and blanking was subjected to solution treatment at a solution temperature of 950°C, a holding time of 2 h, and water quenching.

[0095] 5) Combined deformation heat treatment is performed on the alloy with completed grain refinement, which consists of two deformations and two agings. The plate is cold rolled once at room temperature, with a total cold rolling deformation of 80%, which is completed in three passes, and the deformation of each pass is controlled between 10% and 30%. It is aged once in a furnace at 450°C for 2 hours; it is cold rolled twice at room temperature, with a total cold rolling deformation of 50%, which is completed in three passes, and the deformation of each pass is controlled between 15% and 20%. It is aged twice in a furnace at 350°C for 12 hours.

[0096] The physical properties of the high-strength and high-conductivity copper alloy material prepared in Comparative Example 1 were tested. The final product had a tensile strength of 614 MPa, a hardness of 190 HV, and a conductivity of 76% IACS. The test results are shown in Table 3.

[0097] Table 3 Physical properties of Comparative Example 1

[0098] Physical properties Test Results Test Method Room temperature hardness 190HV YS / T471-2004 Room temperature tensile strength 614MPa GB / T34505-2017 Room temperature elongation 16.9% GB / T34505-2017 Room temperature conductivity 76%IACS GB / T32791-2016

[0099] By comparing the test results of Example 1 with those of Comparative Example 1, it can be seen that the overall comprehensive performance of Comparative Example 1 has been significantly reduced, and this difference is mainly caused by the grain refinement treatment process (the final grain of Example 1 is 3-8 μm, and that of the comparative example is 6-13 μm), indicating that the combination of pre-aging, pre-cooling deformation and regression process can effectively regulate the precipitation order of the precipitated phase, refine the grains of the alloy, and improve the comprehensive performance of the alloy.

[0100] Comparative Example 2

[0101] The components of the CuCrHf alloy material prepared in Comparative Example 2 are the same as those in Example 2. The raw material preparation and smelting process in the preparation method are the same as those in Example 1. The specific processing process is as follows:

[0102] 1) Raw material preparation and smelting are the same as in Example 2.

[0103] 2) The smelted ingot is homogenized and kept at 950°C for 2 hours.

[0104] 3) After the ingot is cooled to 900°C in the furnace, the homogenized billet is subjected to hot processing in the form of hot rolling. The total deformation of the hot rolling is 80%, which is completed in five passes with a deformation of 16% per pass. After the hot rolling, the billet is water quenched.

[0105] 4) The alloy after hot deformation and blanking was solution treated at a solution temperature of 950°C, a holding time of 1 h, and water quenching.

[0106] 5) The alloy with refined grains is subjected to a combined deformation heat treatment, which consists of two deformations and two agings. The plate is cold rolled once at room temperature, with a total cold rolling deformation of 80%, which is completed in three passes, and the deformation of each pass is controlled between 20% and 30%. It is aged once in a furnace at 450°C for 1 hour; it is cold rolled twice at room temperature, with a total cold rolling deformation of 50%, which is completed in three passes, and the deformation of each pass is controlled between 15% and 20%. It is aged twice in a furnace at 350°C for 12 hours, and the new high-strength and high-conductivity copper alloy material studied by the present invention is obtained.

[0107] The physical properties of the high-strength and high-conductivity copper alloy material prepared in Comparative Example 2 were tested. The final product had a tensile strength of 591 MPa, a hardness of 174 HV, and a conductivity of 79% IACS. The test results are shown in Table 4.

[0108] Table 4 Physical properties of Comparative Example 2

[0109] Physical properties Test Results Test Method Room temperature hardness 174HV YS / T471-2004 Room temperature tensile strength 591MPa GB / T34505-2017 Room temperature elongation 18.9% GB / T34505-2017 Room temperature conductivity 79%IACS GB / T32791-2016

[0110] By comparing the test results of Example 2 with those of Comparative Example 2, it is once again verified that the combination of pre-aging, pre-cooling deformation and regression process can effectively regulate the precipitation order of the precipitated phase, refine the grains of the alloy, and improve the comprehensive properties of the alloy.

Claims

1. A high-strength and high-conductivity copper alloy material, characterized in that: The copper alloy material has the following composition, calculated by mass percentage: Cr 0.4-1.5wt.%, Hf 0.6-1.5wt.%, P 0-0.02wt.%, Ce 0-0.15wt.%, Zn 0-0.2wt.%, Ag 0-0.2wt.%, and the balance is Cu.

2. The high-strength and high-conductivity copper alloy material according to claim 1, characterized in that: The copper alloy material has the following composition, calculated by mass percentage: Cr 0.4-0.7wt.%, Hf 0.6-0.9wt.%, P 0-0.02wt.%, Ce 0-0.02wt.%, Zn 0-0.02wt.%, Ag 0-0.2wt.%, and the balance is Cu.

3. A high-strength and high-conductivity copper alloy material according to claim 1 or 2, characterized in that: In the high-strength and high-conductivity copper alloy material, there are interactions between multiple nanoscale precipitated phases and dislocations, which are pinned and entangled with each other and dispersed in the matrix. The grain size of the high-strength and high-conductivity copper alloy material is ≤30μm, and twins are contained in the grains.

4. A method for preparing a high-strength and high-conductivity copper alloy material according to any one of claims 1 to 3, characterized in that: First, various raw materials are prepared according to the designed composition ratio, and smelting is performed to obtain a molten alloy. The molten alloy is cast to obtain a copper alloy ingot. The copper alloy ingot is then subjected to homogenization annealing treatment, thermal deformation treatment, and solid solution treatment in sequence to obtain a solid solution alloy material. Finally, the solid solution alloy material is subjected to pre-aging treatment, pre-cooling deformation treatment, regression treatment, and combined deformation heat treatment in sequence to obtain a high-strength and high-conductivity copper alloy material.

5. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 4, characterized in that: The smelting process comprises: preparing pure copper, Cu-Cr master alloy, Cu-Hf master alloy, Cu-Zn master alloy, Cu-P master alloy, pure Ce, pure Ag and pure Zn according to the designed proportion, firstly melting pure copper, then heating to 1200-1300° C., adding pure Ag and pure Zn, continuing to heat to 1300-1400° C., adding Cu-Cr master alloy in 3-4 batches, keeping the temperature for 2-3 minutes and stirring for 30-60 seconds, then adding Cu-Hf master alloy, pure Ce and Cu-P master alloy, keeping the temperature for 1-2 minutes and cooling to 1200-1300° C. under stirring.

6. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 4 or 5, characterized in that: The smelting is carried out in an atmospheric atmosphere, and graphite is covered on the melt during the smelting process; the casting temperature is 1200-1450°C, and the preheating temperature of the mold is 400-500°C.

7. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 4 or 5, characterized in that: The temperature of the homogenization annealing treatment is 780-980°C, and the time of the homogenization annealing treatment is 2-8h; The thermal deformation treatment is selected from hot forging or hot rolling, the temperature of the thermal deformation treatment is 850-950°C, the total deformation is 50%-90%, and the deformation of each pass is 10%-20%; The temperature of the solution treatment is 800-1050° C., the time of the solution treatment is 2-8 hours, and water quenching is performed after the solution treatment is completed.

8. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 4 or 5, characterized in that: The pre-aging temperature is 350-600°C, and the pre-aging time is 5-480 minutes; The total deformation amount of the pre-cooling deformation treatment is 40% to 90%, and the deformation amount of each pass is 10% to 30%; The temperature of the regression treatment is 750-1000° C., and the time of the regression treatment is 10 s-10 min.

9. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 4 or 5, characterized in that: The combined deformation heat treatment consists of alternating cold deformation treatment and aging treatment.

10. The method for preparing a high-strength and high-conductivity copper alloy material according to claim 9, characterized in that: The combined deformation heat treatment consists of two cold deformations and two aging treatments, wherein the deformation amount of the first cold deformation is 40% to 90%, and the deformation amount of each pass is 10% to 30%. After the first cold deformation treatment, the first aging treatment is performed, and then the second cold deformation treatment is performed. The deformation amount of the second cold deformation treatment is 40% to 90%, and the deformation amount of each pass is 10% to 30%. After the second cold deformation treatment, the second aging treatment is performed, wherein the temperature of the first aging treatment is 350 to 600° C., the time is 5 to 480 min, and the temperature of the second aging treatment is 350 to 600° C., and the time is 5 to 480 min.

Citation Information

Patent Citations

  • Copper alloy trolley cable

    CN102471830A

  • High-strength high-conductivity softening-resistant copper alloy and preparing method thereof

    CN107739878A

  • Copper alloy foil for flexible circuit board

    JP1989056842A

  • High strength and high electric conductivity copper alloy

    JP1994192769A

  • Copper alloy and its production method

    JP2005290543A